VALORACIÓN ECONÓMICA DE LOS SERVICIOS RECREATIVOS DEL "PARQUE DE LA FAMILIA” QUEVEDO-ECUADOR AÑO 2022 - Avellan Sanchez, Lisbeth Yomira (2022)
The economic perspective requires the use of monetary values that can be used in decision-making for planning and conservation of urban parks, which is why the purpose of the research is to determine the economic valuation of the recreational services offered by the park De La Familia, from the city of Quevedo, for which a qualitative-quantitative and bibliographical-documentary methodology is used, which allows to have as a result; improve the services offered in the park so that people visit this important tourist spot more frequently, improve the economy of entrepreneurs and the development of sustainable tourism